Ensuring financial stability: Financial structure and the impact of monetary policy on asset prices - Katrin Assenmacher-Wesche; Stefan Gerlach (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2008)
This paper studies the responses of residential property and equity prices, inflation and economic activity to monetary policy shocks in 17 countries, using data spanning 1986-2006. We estimate VARs for individual economies and panel VARs in which we distinguish between groups of countries on the basis of the characteristics of their financial systems. The results suggest that using monetary policy to offset asset price movements in order to guard against financial instability may have large effects on economic activity. Furthermore, while financial structure influences the impact of policy on asset prices, its importance appears limited. Keywords: asset prices, monetary policy, panel VAR.
urn:nbn:de:hebis:30-70465
Keywords: C23; E52; 330; asset prices; monetary policy; panel VAR